2018
DOI: 10.1093/jn/nxy059
|View full text |Cite
|
Sign up to set email alerts
|

Usual Nutrient Intakes from the Diets of US Children by WIC Participation and Income: Findings from the Feeding Infants and Toddlers Study (FITS) 2016

Abstract: BackgroundA recent report of the National Academies of Sciences, Engineering, and Medicine (NASEM) outlined priority nutrients for infants and children participating in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC).ObjectiveThe objective of this study was to assess usual nutrient intakes from foods and beverages (not supplements) among US children aged <4 y by WIC participation status.MethodsA national random sample of children aged <4 y (n = 3,235) from the Feeding Infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 36 publications
0
41
0
1
Order By: Relevance
“…Our data suggest that among children aged ≥12 mo it is difficult to obtain the recommended vitamin D intakes without the use of supplements. FITS 2016 data presented elsewhere in this supplement also suggest that children <4 y old who are participating in WIC have more optimal vitamin D intakes than those who are not ( 25 ). It should be noted that estimates of vitamin D inadequacy from the diet are often higher than that of estimates from serum 25 (OH) vitamin D (which includes the contribution of sunlight exposure), but little is known about the relation between dietary intakes and biomarkers of vitamin D exposure in infants ( 38 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our data suggest that among children aged ≥12 mo it is difficult to obtain the recommended vitamin D intakes without the use of supplements. FITS 2016 data presented elsewhere in this supplement also suggest that children <4 y old who are participating in WIC have more optimal vitamin D intakes than those who are not ( 25 ). It should be noted that estimates of vitamin D inadequacy from the diet are often higher than that of estimates from serum 25 (OH) vitamin D (which includes the contribution of sunlight exposure), but little is known about the relation between dietary intakes and biomarkers of vitamin D exposure in infants ( 38 ).…”
Section: Discussionmentioning
confidence: 93%
“…Dietary data without the inclusion of dietary supplement overestimates the prevalence of inadequacy (i.e., % <EAR) and underestimates the prevalence of potentially excessive intakes (i.e., >UL) ( 22–24 ). Estimates of nutrient intakes from foods alone by age group can be found in the Supplemental Tables 2–6 and stratified by WIC participation in Jun et al ( 25 ) in this supplement.…”
Section: Methodsmentioning
confidence: 99%
“…Bailey et al ( 18 ) do not break out nutrient intakes by food source, so these iron results cannot be definitively linked to consumption rates for these foods at this time, but they are consistent and suggest avenues for future investigation. In contrast, Jun et al ( 19 ) found that WIC participants were less likely to be at risk of iron deficiency than nonparticipants.…”
Section: Key Findingsmentioning
confidence: 90%
“…WIC children were more likely to shift to lower-fat milk options at age 2 y, consistent with expert recommendations, but they were also considerably more likely to consume fruit juice than non-WIC children were ( 13 ). Usual nutrient intakes of WIC toddlers and young children were adequate, and WIC children had higher intakes of iron and lower risk of iron deficiency at all ages ( 19 ), but there is room for improvement in other respects: WIC children at all ages had higher sodium intakes than non-WIC participants, and their vitamin A (retinol) and zinc intakes exceeded the tolerable upper limit more often.…”
Section: Key Findingsmentioning
confidence: 99%
“…The new WIC program regulations included steps such as eliminating fruit juice from the infant package, additional promotion of breastfeeding initiation and duration, and routine switch to low- or nonfat milk for older children. All of this is summarized in detail in the paper by Guthrie et al ( 39 ) for foods and that by Jun et al ( 40 ) for nutrients. These findings demonstrate opportunities for improvements in dietary intake in WIC participants and to improve the WIC system of nutrition education and supplement foods.…”
Section: Highlights Of Fits 2016mentioning
confidence: 99%